TRADISI BUDAYA DAN TRADISI AGAMA DALAM KEHIDUPAN SOSIAL - Syamsuriah Syamsuriah (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2013)
Culture is part of the tradition but samawi religion is not part of culture, because the religion of Islam reaches two relations are vertical and horizontal, human relations and trancendental relations (to God). Islam as a samawi religion is not part of the culture, and Islamic culture is not part of religion of Islam, each one stands alone, but there is a strong correlation between them. Islam is the foundation, principles, and controllers are sources of cultural calues in cultural development. Islamic religious culture provides stimulation for movement, so a patterned culture and identity does not develop into a civilizationof Islam became established and growing civilization or culture in moslem society.